Perception of Human Cadaver Dissection by MBBS Students of a Medical College in Nepal (Journal of Nobel Medical College, 2025)
Background: Cadaveric dissection has traditionally played a central role in anatomical teaching pedagogy due to being immersive in nature and providing hands-on experience to students. Recent advancements have sparked debates about the replacement of dissection-based learning by the modern technology assisted learning tools in contemporary anatomy curricula. This study aims to systematically explore the perspectives of second- and third-year MBBS students in a Nepali medical college towards the usage of cadaveric dissection as a learning tool in anatomy education.Materials and Methods: A descriptive cross-sectional study was conducted to explore the perception of MBBS students regarding the dissection. The study included 115 MBBS students currently in their second or third year who have a minimum of one year of experience in cadaveric dissection and have been actively involved in dissection-based learning activities within the last two academic years. A structured, questionnaire comprising 26 Likert-scale items was used to assess the students' perception, attitude, and response to cadaveric dissection. The responses were coded, entered and analysed. Chi-square tests were applied to assess the association between variables.Results: Out of 115 participants, 73.0% strongly agreed that their first visit to the dissection room was exciting, 86.1% agreed or strongly agreed that dissection deepened their understanding of anatomical concepts, 96% of the students agreed that dissection enhanced their respect for the human body, 93.9% said it made learning more interesting, 92.1% acknowledged that dissection helped them recall what they learned, 88.2% felt it provided them with lasting knowledge and 92.2% acknowledged three-dimensional understanding of body structures gained through dissection. Among the total participants, 94.8% believed they would be disadvantaged if they missed out on dissection.Conclusion: The findings of this study suggests that cadaveric dissection is perceived by MBBS students as essential and irreplaceable component of anatomy education and should be integrated as learning tool for anatomy curriculum.